Non‐motor symptom burden is strongly correlated to motor complications in patients with Parkinson's disease. (24th April 2020) - Santos‐García, D.; de Deus Fonticoba, T.; Suárez Castro, E.; Aneiros Díaz, A.; McAfee, D.; Catalán, M. J.; Alonso‐Frech, F.; Villanueva, C.; Jesús, S.; Mir, P.; Aguilar, M.; Pastor, P.; et al.
Abstract : Background and purpose: The objective of this study was to analyze the relationship between motor complications and non‐motor symptom (NMS) burden in a population of patients with Parkinson's disease (PD) and also in a subgroup of patients with early PD. Methods: Patients with PD from the COPPADIS cohort were included in this cross‐sectional study. NMS burden was defined according to the Non‐Motor Symptoms Scale (NMSS) total score. Unified Parkinson's Disease Rating Scale (UPDRS) part IV was used to establish motor complication types and their severity. Patients with ≤5 years of symptoms from onset were included as patients with early PD. Results: Of 690 patients with PD (62.6 ± 8.9 years old, 60.1% males), 33.9% and 18.1% presented motor fluctuations and dyskinesia, respectively. The NMS total score was higher in patients with motor fluctuations (59.2 ± 43.1 vs. 38.3 ± 33.1; P  < 0.0001) and dyskinesia (63.5 ± 40.7 vs. 41.4 ± 36.3; P  < 0.0001). In a multiple linear regression model and after adjustment for age, sex, disease duration, Hoehn & Yahr stage, UPDRS‐III score and levodopa equivalent daily dose, UPDRS‐IV score was significantly related to a higher NMSS total score ( β  = 0.27; 95% confidence intervals, 2.81–5.61; P  < 0.0001), as it was in a logistic regression model on dichotomous NMSS total score (≤40, mild or moderate vs. >40, severe or very severe) (odds ratio, 1.31; 95% confidence intervals, 1.17–1.47; P  < 0.0001). In the subgroup of patients with early PD ( n  = 396; mean disease duration 2.7 ± 1.5 years), motor fluctuations were frequent (18.1%) and similar results were obtained. Conclusions: Motor complications were frequent and were associated with a greater NMS burden in patients with PD even during the first 5 years of disease duration.